2019
DOI: 10.4187/respcare.06770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Hormone Treatment on Diaphragmatic Efficiency in Mechanically Ventilated Subjects With Nonthyroidal Illness Syndrome

Abstract: BACKGROUND: Several respiratory abnormalities can be present in primary hypothyroidism and can be reversed with adequate hormone treatment. However, the role of thyroid hormone replacement therapy on the respiratory system in patients with nonthyroidal illness syndrome is still unclear. This physiologic study evaluated the effect of thyroid hormone treatment on respiratory muscle function in subjects with nonthyroidal illness syndrome and while on mechanical ventilation. The primary end point was neuromechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…The authors concluded that thyroid hormone replacement did not benefit critically ill subjects with NTIS. 20 These results do not support further evaluation of the role of thyroid replacement for patients with NTIS and add to other work suggesting that NTIS may be adaptive, rather than pathological.…”
contrasting
confidence: 83%
See 3 more Smart Citations
“…The authors concluded that thyroid hormone replacement did not benefit critically ill subjects with NTIS. 20 These results do not support further evaluation of the role of thyroid replacement for patients with NTIS and add to other work suggesting that NTIS may be adaptive, rather than pathological.…”
contrasting
confidence: 83%
“…17 The contribution of NTIS to respiratory failure and whether thyroid hormone replacement improves respiratory muscle function remains unknown, and thyroid hormone replacement in critically ill patients with NTIS has not been shown to improve outcomes. 18,19 The paper by Bello and colleagues 20 in this issue of the Journal takes nonthyroidal illness, common in the ICU and potentially linked to respiratory muscle function, and uses diaphragmatic neuromuscular efficiency (NME) as a surrogate end point, seeking to show whether a larger clinical trial is worthwhile.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, T3 treatment did not affect mortality in patients suffering from acute burn injury [35]. T3 infusion in mechanically ventilated patients with NTIS also did not affect respiratory muscle function [36]. In acutely ill patients with low serum T4 levels, T4 treatment did not affect mortality [37] or even increased it [38].…”
Section: Ntis In Critically Ill Adults Treated In the Intensive Camentioning
confidence: 99%